Lexicon and its Essential Subtypes in English Language (The Peerian Journal, 2022)
Over recent years there has been much interest in the sphere of distributional semantics, focusing on the distributional hypothesis: words that occur in similar contexts tend to have similar meanings (Harris, 1954). There is a large body of work on the use of different similarity measures (Lee, 1999; Weeds and Weir, 2003; Curran, 2004) and many researchers have built thesauri (i.e., lists of “nearest neighbours”) automatically and applied them in a variety of applications, generally with a good deal of success.